Progressive cognitive impairment after recovery from neuroinvasive and non-neuroinvasive Listeria monocytogenes infection - Cassidy, Benjamin R.; Logan, Sreemathi; Farley, Julie A.; Owen, Daniel B.; Sonntag, William E.; Drevets, Douglas A. (Frontiers in Immunology, 2023)
Background: Neuro-cognitive impairment is a deleterious complication of bacterial infections that is difficult to treat or prevent. Listeria monocytogenes (Lm) is a neuroinvasive bacterial pathogen and commonly used model organism for studying immune responses to infection. Antibiotic-treated mice that survive systemic Lm infection have increased numbers of CD8+ and CD4+ T-lymphocytes in the brain that include tissue resident memory (TRM) T cells, but post-infectious cognitive decline has not been demonstrated. We hypothesized that Lm infection would trigger cognitive decline in accord with increased numbers of recruited leukocytes. Methods: Male C57BL/6J mice (age 8 wks) were injected with neuroinvasive Lm 10403s, non-neuroinvasive Δhly mutants, or sterile saline. All mice received antibiotics 2-16d post-injection (p.i.) and underwent cognitive testing 1 month (mo) or 4 mo p.i. using the Noldus PhenoTyper with Cognition Wall, a food reward-based discrimination procedure using automated home cage based observation and monitoring. After cognitive testing, brain leukocytes were quantified by flow cytometry. Results: Changes suggesting cognitive decline were observed 1 mo p.i. in both groups of infected mice compared with uninfected controls, but were more widespread and significantly worse 4 mo p.i. and most notably after Lm 10403s. Impairments were observed in learning, extinction of prior learning and distance moved. Infection with Lm 10403s, but not Δhly Lm, significantly increased numbers of CD8+ and CD4+ T-lymphocytes, including populations expressing CD69 and TRM cells, 1 mo p.i. Numbers of CD8+, CD69+CD8+ T-lymphocytes and CD8+ TRM remained elevated at 4 mo p.i. but numbers of CD4+ cells returned to homeostatic levels. Higher numbers of brain CD8+ T-lymphocytes showed the strongest correlations with reduced cognitive performance. Conclusions: Systemic infection by neuroinvasive as well as non-neuroinvasive Lm triggers a progressive decline in cognitive impairment. Notably, the deficits are more profound after neuroinvasive infection that triggers long-term retention of CD8+ T-lymphocytes in the brain, than after non-neuroinvasive infection, which does not lead to retained cells in the brain. These results support the conclusion that systemic infections, particularly those that lead to brain leukocytosis trigger a progressive decline in cognitive function and implicate CD8+ T-lymphocytes, including CD8+TRM in the etiology of this impairment.